Loyalty of Village Officials in the Implementation of Main Duties and Functions in Hiyalo Oyile Village, Anggrek District, North Gorontalo Regency - Sardin R Kino (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine the Loyalty of Village Officials in the Implementation of Main Tasks and Functions in Hiyalo Oyile Village, Anggrek District, North Gorontalo Regency. The data analysis technique used is a qualitative analysis technique. The results of the study show that the Loyalty of Village Apparatuses in the Implementation of Main Duties and Functions seen from the aspects of obedience to rules, responsibilities, and the ability to cooperate has not been maximized and has not supported the Implementation of Main Duties and Functions. As for the things suggested in this study, namely the need for the village government to always obey all rules, be responsible for tasks, and always cooperate in carrying out organizational tasks, so that the implementation of main tasks and functions can be realized professionally, independently, effectively and accountably.